2014
DOI: 10.1097/qai.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Immunological Recovery Among Older Adults on Antiretroviral Therapy at a Large Urban HIV Clinic in Kampala, Uganda

Abstract: Background We describe older (> 50 years) HIV-infected adults after ART initiation, evaluating immunological recovery by age category, considering individual trajectories based on the pre-treatment CD4. We also describe mortality on ART and its risk factors by age category including the contribution of poor immunological recovery at a large urban clinic in Kampala, Uganda. Methods We performed a cohort analysis of adult (>18 years) HIV-infected patients who initiated ART between January 1, 2004 and January 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
11
15
0
Order By: Relevance
“…Unsurprisingly, most deaths occurred in the first 24 months post ART initiation. The mortality in the first 12 months did not differ significantly in both groups and is in keeping with other reports from sub Saharan Africa where high mortality is reported following initial initiation of ART [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…Unsurprisingly, most deaths occurred in the first 24 months post ART initiation. The mortality in the first 12 months did not differ significantly in both groups and is in keeping with other reports from sub Saharan Africa where high mortality is reported following initial initiation of ART [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…Multiple studies have demonstrated that, despite successful ART and viral suppression, immune recovery is less robust with increasing age, highlighting the importance of early diagnosis and treatment of HIV [16,[29][30][31][32]. Consistent with previous studies, patients aged ≥50 years with comorbidities in our study had a greater rate of immunological failure compared to patients <50 years with comorbidities.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, Teixeira et al, [28] and Lawn et al, [29] showed that age above 30 years is associated with sub-optimal CD4. Different studies [4,[30][31][32] have also shown association of older age with A c c e p t e d M a n u s c r i p t 10 lower CD4 counts at similar time from seroconversion which may explain the relationship between age and disease progression. Furthermore, Ferrer et al, [33] and Gras et al, [25] in different studies associated older age (≥50 years) with immune reconstitution failure and plateau in CD4 cell restoration.…”
Section: Discussionmentioning
confidence: 92%